SMALL CITIES, VILEGIATURE AND URBANIZATION IN NORTHEAST BRAZIL - Gomes, Iara Rafaela; Oliveira, Paulo Roberto Abreu de (Geosaberes, 2021)
The article deals with the practice of vilegiature and how it redefines the urban dynamics of small cities, as well as its role in the urban network. The focus of the study was based on small mountain and coastal cities located in northeastern Brazil. Gravatá (PE), Guaramiranga (CE), Lagoa Nova (RN) and Tibau (RN) show this phenomenon in recent years, which indicates how the leisure society appropriates the beach and the mountains, establishing strong territorial ties with non-metropolitan spaces, conceiving indispensable factors of comfort and convenience imposed by urban society. The research was built by consulting virtual bibliographic collections, books and elaborating and analyzing a statistical database obtained, in particular, from the Brazilian Institute of Geography and Statistics - IBGE, as well as fieldwork in the cities studied.